Research of the foreign countries experience in regulation of investment processes in building sphere - Shlafman, N.; Frolina, K. (Економічний вісник Донбасу, 2017)
The article describes the study of the experience of foreign countries in the regulation of investment processes in the construction industry. Analysis of the experience of foreign countries in the field of state regulation and stimulation of investment in construction can help develop new, effective mechanisms for implementing state policy in the field of residential, industrial and infrastructure construction, establishing and expanding international cooperation in the construction sector, creating opportunities for attracting investment in housing and industrial construction, including foreign ones. The analysis of housing financing systems in developed countries of the world (USA, England, Germany, France) shows that they are based on a variety of specialized financial institutions - construction and savings, mortgage companies, investment banks, credit unions, as well as on several financial technologies: construction savings, mortgage lending, a certain combination of other, public and private financing, as well as various mixed forms of public and private funding. In these countries the state possesses and active market instruments of state regulation of investment processes through mortgage markets, secondary loans using state (or semi-public) financial institutions. The analysis of the state of legal regulation in the investment sphere of Ukraine, the development of the securities market and investment trends in the real estate market, and the practice of state regulation of investment and construction processes in Ukraine testify to the expediency of adapting the experience of developed countries to the methods of state regulation of investment activity in the construction sphere to Ukraine, which may become an essential direction of intensification of investment processes in the country.